Investigation of foot biomechanics in youth basketball players - Hamza Sinen; Berkay Üzümcü; Yusuf Yaşasın; Görkem Açar; Sinan Seyhan (Turkish Journal of Kinesiology)
This study aimed to evaluate foot biomechanics and plantar pressure in youth basketball players. The study included 70 male basketball players under the age of 18 years. Plantar pressure percentage distribution, hallux valgus angle (HVA), navicular drop test (NDT), subtalar pronation angle (SPA) and knee valgus angle (KVA) were measured. The data were subjected to homogeneity analysis using the Shapiro-Wilk test, and a Pearson correlation test was subsequently applied. Plantar pressure distribution was even. Moderate hallux valgus and subtalar pronation tendency were observed in both feet. NDT was positive, but the KVA was normal. Strong positive correlations were found between HVA, SPA, KVA, and NDT. There is a tendency for hallux valgus, subtalar pronation, and flatfoot in youth basketball players. These findings suggest that young athletes may be at risk for ankle and knee problems. Therefore, early preventive measures and regular foot biomechanical evaluations are recommended.